Governing global health challenge, response, innovation - Cooper, Andrew Fenton; Kirton, John J.; Schrecker, Ted (Global environmental governance series, 2007)
Presents a study of the global challenges and responses to the issues of global health, as well as the roles of central institutions such as the World Health Organization, the World Trade Organization and the G8. This book is suitable for health practitioners and clinicians seeking a context for their front-line care provision.